Health literacy and 30-day hospital readmission after acute myocardial infarction. Issue 6 (11th June 2015) - Bailey, Stacy Cooper; Fang, Gang; Annis, Izabela E; O'Conor, Rachel; Paasche-Orlow, Michael K; Wolf, Michael S
Abstract : Objective: To assess the validity of a predictive model of health literacy, and to examine the relationship between derived health literacy estimates and 30-day hospital readmissions for acute myocardial infarction (AMI). Design: Retrospective cohort study. Setting and participants: A National Institute of Aging (NIA) study cohort of 696 adult, English-speaking primary care patients, aged 55–74 years, was used to assess the validity of derived health literacy estimates. Claims from 7733 Medicare beneficiaries hospitalised for AMI in 2008 in North Carolina and Illinois were used to investigate the association between health literacy estimates and 30-day hospital readmissions. Measures: The NIA cohort was administered 3 common health literacy assessments (Newest Vital Sign, Test of Functional Health Literacy in Adults, and Rapid Estimate of Adult Literacy in Medicine). Health literacy estimates at the census block group level were derived via a predictive model. 30-day readmissions were measured from Medicare claims data using a validated algorithm. Results: Fair agreement was found between derived estimates and in-person literacy assessments (Pearson Correlation coefficients: 0.38–0.51; κ scores: 0.38–0.40). Medicare enrollees with above basic literacy according to derived health literacy estimates had an 18% lower risk of a 30-day readmission (RR=0.82, 95% CI 0.73 to 0.92) and 21% lower incidence rate of 30-day readmission (IRR=0.79, 95% CI 0.68 to 0.87) than patients with basic or below basic literacy. After adjusting for demographic and clinical characteristics, the risk of 30-day readmission was 12% lower (p=0.03), and the incidence rate 16% lower (p<0.01) for patients with above basic literacy. Conclusions: Health literacy, as measured by a predictive model, was found to be a significant, independent predictor of 30-day readmissions. As a modifiable risk factor with evidence-based solutions, health literacy should be considered in readmission reduction efforts.